You are on page 1of 118

# VECTOR FUNCTIONS

VECTOR FUNCTIONS

12.4
Motion in Space:
Velocity and Acceleration
In this section, we will learn about:
The motion of an object
using tangent and normal vectors.

## Here, we show how the ideas of tangent

and normal vectors and curvature can be
used in physics to study:
The motion of an object, including its velocity
and acceleration, along a space curve.

## In particular, we follow in the footsteps of

Newton by using these methods to derive
Keplers First Law of planetary motion.

VELOCITY

## Suppose a particle moves through

space so that its position vector at
time t is r(t).

VELOCITY

Vector 1

## Notice from the figure that, for small values

of h, the vector

r (t + h) r (t )
h
approximates
the direction of the
particle moving along
the curve r(t).

VELOCITY

## Its magnitude measures the size

of the displacement vector per unit
time.

VELOCITY

## The vector 1 gives the average

velocity over a time interval of
length h.

VELOCITY VECTOR

Equation 2

at time t :

r (t + h) r (t )
v (t ) = lim
h 0
h
= r '(t )

VELOCITY VECTOR

## Thus, the velocity vector is also

the tangent vector and points in
the direction of the tangent line.

SPEED

## The speed of the particle at time t

is the magnitude of the velocity vector,
that is, |v(t)|.

SPEED

## This is appropriate because, from Equation 2

and from Equation 7 in Section 12.3,
we have:

ds
| v(t ) |=| r '(t ) |=
dt
= rate of change
of distance with
respect to time

ACCELERATION

## As in the case of one-dimensional motion,

the acceleration of the particle is defined as
the derivative of the velocity:
a(t) = v(t) = r(t)

Example 1

## The position vector of an object moving

in a plane is given by:
r(t) = t3 i + t2 j
Find its velocity, speed, and acceleration
when t = 1 and illustrate geometrically.

Example 1

## The velocity and acceleration at time t

are:
v(t) = r(t) = 3t2 i + 2t j
a(t) = r(t) = 6t I + 2 j

Example 1

## The speed at t is:

| v (t ) |= (3t ) + (2t )
2 2

= 9t + 4t
4

## VELOCITY & ACCELERATION

Example 1

When t = 1, we have:
v(1) = 3 i + 2 j
a(1) = 6 i + 2 j
|v(1)| = 13

Example 1

are shown here.

Example 2

## Find the velocity, acceleration, and

speed of a particle with position vector
r(t) = t2, et, tet

Example 2

## VELOCITY & ACCELERATION

v (t ) = r '(t ) = 2t , e , (1 + t )e
t

a(t ) = v '(t ) = 2, e , (2 + t )e
t

| v (t ) |= 4t + e + (1 + t ) e
2

2t

2t

## The figure shows the path of the particle in

Example 2 with the velocity and acceleration
vectors when t = 1.

## The vector integrals that were introduced in

Section 12.2 can be used to find position
vectors when velocity or acceleration vectors
are known, as in the next example.

Example 3

## A moving particle starts at an initial position

r(0) = 1, 0, 0
with initial velocity
v(0) = i j + k
Its acceleration is
a(t) = 4t i + 6t j + k
Find its velocity and position at time t.

Example 3

## Since a(t) = v(t), we have:

v(t) = a(t) dt
= (4t i + 6t j + k) dt
=2t2 i + 3t2 j + t k + C

Example 3

## To determine the value of the constant

vector C, we use the fact that
v(0) = i j + k

So,
C=ij+ k

## VELOCITY & ACCELERATION

Example 3

It follows:
v(t) = 2t2 i + 3t2 j + t k + i j + k
= (2t2 + 1) i + (3t2 1) j + (t + 1) k

Example 3

## Since v(t) = r(t), we have:

r(t) = v(t) dt
= [(2t2 + 1) i + (3t2 1) j + (t + 1) k] dt
= (t3 + t) i + (t3 t) j + (t2 + t) k + D

Example 3

## Putting t = 0, we find that D = r(0) = i.

So, the position at time t is given by:
r(t) = (t3 + t + 1) i + (t3 t) j + (t2 + t) k

## The expression for r(t) that we obtained

in Example 3 was used to plot the path
of the particle here for 0 t 3.

## In general, vector integrals allow us

to recover:
Velocity, when acceleration is known
t

v (t ) = v (t0 ) + a(u ) du
t0

## Position, when velocity is known

t

r (t ) = r (t0 ) + v (u ) du
t0

## If the force that acts on a particle is known,

then the acceleration can be found from
Newtons Second Law of Motion.

## The vector version of this law states that if,

at any time t, a force F(t) acts on an object
of mass m producing an acceleration a(t),
then
F(t) = ma(t)

Example 4

## An object with mass m that moves in

a circular path with constant angular speed
has position vector
r(t) = a cos t i + a sin t j

## Find the force acting on the object and

show that it is directed toward the origin.

Example 4

## To find the force, we first need to know

the acceleration:

## v(t) = r(t) = a sin t i + a cos t j

a(t) = v(t) = a2 cos t i a2 sin t j

Example 4

## Therefore, Newtons Second Law gives

the force as:
F(t) = ma(t)
= m2 (a cos t i + a sin t j)

## VELOCITY & ACCELERATION

Example 4

Notice that:
F(t) = m2r(t)
This shows that the force acts in the direction
opposite to the radius vector r(t).

Example 4

## Therefore, it points toward

the origin.

CENTRIPETAL FORCE

Example 4

## Such a force is called a centripetal

(center-seeking) force.

Example 5

## A projectile is fired with:

Angle of elevation
Initial velocity v0

Example 5

## Assuming that air resistance is negligible

and the only external force is due to gravity,
find the position function r(t) of the projectile.

Example 5

## What value of maximizes the range

(the horizontal distance traveled)?

Example 5

## We set up the axes so that the projectile

starts at the origin.

Example 5

## As the force due to gravity acts downward,

we have:
F = ma = mg j
where g = |a| 9.8 m/s2.
Therefore, a = g j

Example 5

## Since v(t) = a, we have:

v(t) = gt j + C
where C = v(0) = v0.
Therefore,
r(t) = v(t) = gt j + v0

Example 5

## Integrating again, we obtain:

r(t) = gt2 j + t v0 + D
However,
D = r(0) = 0

## VELOCITY & ACCELERATION

E. g. 5Equation 3

## So, the position vector of the projectile

is given by:
r(t) = gt2 j + t v0

Example 5

## If we write |v0| = v0 (the initial speed

of the projectile), then
v0 = v0 cos i + v0 sin j
Equation 3 becomes:
r(t) = (v0 cos )t i + [(v0 sin )t gt2] j

## VELOCITY & ACCELERATION

E. g. 5Equations 4

## Therefore, the parametric equations

of the trajectory are:
x = (v0 cos )t
y = (v0 sin )t gt2

Example 5

## If you eliminate t from Equations 4,

you will see that y is a quadratic function
of x.

Example 5

of a parabola.

Example 5

## The horizontal distance d is the value

of x when y = 0.

Setting y = 0, we obtain:
t = 0 or t = (2v0 sin )/g

Example 5

## That second value of t then gives:

2v0 sin
d = x = (v0 cos )
g
v (2sin cos ) v sin 2
=
=
g
g
2
0

2
0

## Clearly, d has its maximum value when

sin 2 = 1, that is, = /4.

Example 6

## A projectile is fired with muzzle speed 150 m/s

and angle of elevation 45 from a position
10 m above ground level.
Where does the projectile hit the ground?
With what speed does it do so?

Example 6

## If we place the origin at ground level,

the initial position of the projectile is (0, 10).

## So, we need to adjust Equations 4

by adding 10 to the expression for y.

Example 6

we have:

## x = 150 cos( / 4)t = 75 2 t

y = 10 + 150sin( / 4)t (9.8)t
1
2

= 10 + 75 2 t 4.9t

Example 6

## Impact occurs when y = 0, that is,

4.9t2 75 2 t 10 = 0

## Solving this quadratic equation (and using

only the positive value of t), we get:

t=
21.74
9.8

Example 6

Then,
x 75 2 (21.74)
2306

Example 6

## The velocity of the projectile is:

v(t ) = r '(t )
= 75 2 i + (75 2 9.8t ) j

Example 6

## | v (21.74) |= (75 2) + (75 2 9.8 21.74)

2

151m/s

ACCELERATIONCOMPONENTS

## When we study the motion of a particle,

it is often useful to resolve the acceleration
into two components:
Tangential (in the direction of the tangent)
Normal (in the direction of the normal)

ACCELERATIONCOMPONENTS

## If we write v = |v| for the speed of the particle,

then

r '(t )
v (t )
v
T(t ) =
=
=
| r '(t ) | | v (t ) | v
Thus,
v = vT

ACCELERATIONCOMPONENTS

Equation 5

## If we differentiate both sides of that

equation with respect to t, we get:

## a = v ' = v ' T + vT '

ACCELERATIONCOMPONENTS

Equation 6

## If we use the expression for the curvature

given by Equation 9 in Section 12.3,
we have:

| T'| | T'|
so | T ' |= v
=
=
|r'|
v

ACCELERATIONCOMPONENTS

## The unit normal vector was defined

in Section 12.4 as N = T/ |T|
So, Equation 6 gives:

T ' =| T ' | N = vN

ACCELERATIONCOMPONENTS

Formula/Equation 7

## Then, Equation 5 becomes:

a = v 'T + v N
2

ACCELERATIONCOMPONENTS

Equations 8

## Writing aT and aN for the tangential and

normal components of acceleration,
we have
a = aTT + aNN
where
aT = v

and

aN = Kv2

ACCELERATIONCOMPONENTS

## This resolution is illustrated

here.

ACCELERATIONCOMPONENTS

## Lets look at what Formula 7

says.

a = v 'T + v N
2

ACCELERATIONCOMPONENTS

## The first thing to notice is that

the binormal vector B is absent.
No matter how an object moves through space,
its acceleration always lies in the plane of T and N
(the osculating plane).
Recall that T gives the direction of motion and
N points in the direction the curve is turning.

ACCELERATIONCOMPONENTS

## Next, we notice that:

The tangential component of acceleration is v,
the rate of change of speed.
The normal component of acceleration is v2,
the curvature times the square of the speed.

ACCELERATIONCOMPONENTS

## This makes sense if we think of

a passenger in a car.
A sharp turn in a road means a large value
of the curvature .
So, the component of the acceleration perpendicular
to the motion is large and the passenger is thrown
against a car door.

ACCELERATIONCOMPONENTS

## High speed around the turn has

the same effect.
In fact, if you double your speed,
aN is increased by a factor of 4.

ACCELERATIONCOMPONENTS

## We have expressions for the tangential

and normal components of acceleration in
Equations 8.
However, its desirable to have expressions
that depend only on r, r, and r.

ACCELERATIONCOMPONENTS

## Thus, we take the dot product of v = vT

with a as given by Equation 7:
v a = vT (v T + v2N)
= vv T T + v3T N
= vv

(Since T T = 1 and T N = 0)

ACCELERATIONCOMPONENTS

Equation 9

Therefore,

v a
aT = v ' =
v
r '(t ) r "(t )
=
| r '(t ) |

ACCELERATIONCOMPONENTS

Equation 10

## Using the formula for curvature given by

Theorem 10 in Section 12.3, we have:

| r '(t ) r "(t ) |
2
aN = v =
| r '(t ) |
3
| r '(t ) |
| r '(t ) r "(t ) |
=
| r '(t ) |
2

ACCELERATIONCOMPONENTS

Example 7

## A particle moves with position function

r(t) = t2, t2, t3

## Find the tangential and normal

components of acceleration.

ACCELERATIONCOMPONENTS
2

r (t ) = t i + t j + t k
2

r '( t ) = 2 t i + 2 t j + 3 t k
r "( t ) = 2 i + 2 j + 6 t k
| r'( t ) | =

8t + 9t
2

Example 7

Example 7

ACCELERATIONCOMPONENTS

## Therefore, Equation 9 gives the tangential

component as:

r '(t ) r "(t )
aT =
| r '(t ) |
=

8t + 18t

8t + 9t
2

ACCELERATIONCOMPONENTS

i
r '(t ) r "(t ) = 2t
2

2t 3t
2

6t

= 6t i 6t j
2

Example 7

Example 7

ACCELERATIONCOMPONENTS

component as:

r '(t ) r "(t )
aN =
| r '(t ) |
=

6 2t

8t + 9t
2

## We now describe one of the great

accomplishments of calculus by showing how
the material of this chapter can be used to
prove Keplers laws of planetary motion.

## After 20 years of studying the astronomical

observations of the Danish astronomer
Tycho Brahe, the German mathematician and
astronomer Johannes Kepler (15711630)
formulated the following three laws.

## A planet revolves around the sun

in an elliptical orbit with the sun at
one focus.

## The line joining the sun to

a planet sweeps out equal areas
in equal times.

## The square of the period of revolution

of a planet is proportional to the cube
of the length of the major axis of its orbit.

KEPLERS LAWS

## In his book Principia Mathematica of 1687,

Sir Isaac Newton was able to show that
these three laws are consequences of
two of his own laws:
Second Law of Motion
Law of Universal Gravitation

## In what follows, we prove Keplers

First Law.
The remaining laws are proved
as exercises (with hints).

## The gravitational force of the sun on a planet

is so much larger than the forces exerted by
other celestial bodies.

## Thus, we can safely ignore all bodies in

the universe except the sun and one planet

## We use a coordinate system with the sun

at the origin.
We let r = r(t) be the position vector
of the planet.

## Equally well, r could be the position

vector of any of:
The moon
A satellite moving around the earth
A comet moving around a star

## The velocity vector is:

v = r
The acceleration vector is:
a = r

## We use the following laws of Newton.

Second Law of Motion:

F = ma

Law of Gravitation:

GMm
F= 3 r
r
GMm
= 2 u
r

## In the two laws,

F is the gravitational force on the planet
m and M are the masses of the planet and the sun
G is the gravitational constant
r = |r|
u = (1/r)r is the unit vector in the direction of r

## First, we show that

the planet moves in
one plane.

## By equating the expressions for F in

Newtons two laws, we find that:

GM
a= 3 r
r
So, a is parallel to r.
It follows that r x a = 0.

## We use Formula 5 in Theorem 3 in

Section 12.2 to write:

d
(r v ) = r ' v + r v '
dt
= v v + ra
= 0+0
=0

## KEPLERS FIRST LAWPROOF

Therefore,
rxv=h
where h is a constant vector.
We may assume that h 0;
that is, r and v are not parallel.

## This means that the vector r = r(t) is

perpendicular to h for all values of t.

## So, the planet always lies in the plane through

the origin perpendicular to h.

a plane curve.

## To prove Keplers First Law, we rewrite

the vector h as follows:

h = r v = rr '
= r u (r u) '
= r u (ru '+ r ' u)
= r (u u ') + rr '(u u)
2

= r (u u ')
2

## KEPLERS FIRST LAWPROOF

Then,
GM
2
a h = 2 u (r u u ')
r
= GM u (u u ')
= GM [ (u u ')u (u u)u ']

(Property 6,
Th. 8, Sec. 11.4)

## KEPLERS FIRST LAWPROOF

However, u u = |u|2 = 1
Also, |u(t)| = 1

that:
u u = 0

Therefore,

a h = GM u '
Thus,

Equation 11

## Integrating both sides of that equation,

we get:

v h = GM u + c
where c is a constant vector.

## At this point, it is convenient to choose the

coordinate axes so that the standard basis
vector k points in the direction of the vector h.

## As both v x h and u are perpendicular

to h, Equation 11 shows that c lies in
the xy-plane.

## This means that we can choose

the x- and y-axes so that the vector i
lies in the direction of c.

## If is the angle between c and r,

then (r, ) are polar coordinates of
the planet.

## From Equation 11 we have:

r ( v h) = r (GM u + c)
= GM r u + r c
= GMr u u + | r || c | cos
= GMr + rc cos
where c = |c|.

## KEPLERS FIRST LAWPROOF

Then,

r ( v h)
r=
GM + c cos
1 r ( v h)
=
GM 1 + e cos
where e = c/(GM).

## KEPLERS FIRST LAWPROOF

However,

r ( v h) = (r v ) h
= h h
=| h |

=h
where h = |h|.

Thus,
2

h /(GM )
r=
1 + e cos
2
eh / c
=
1 + e cos

Equation 12

ed
r=
1 + e cos

## Comparing with Theorem 6 in Section 10.6,

we see that Equation 12 is the polar equation
of a conic section with:
Focus at the origin
Eccentricity e

a closed curve.

## This completes the derivation

of Keplers First Law.

KEPLERS LAWS

## The proofs of the three laws show that

the methods of this chapter provide
a powerful tool for describing some
of the laws of nature.